Design and engineering of artificial microbial consortia for biohydrogen production. (February 2022) - Ergal, İpek; Bochmann, Günther; Fuchs, Werner; Rittmann, Simon K-MR
Graphical abstract: Highlights: A precision design pipeline for artificial consortium engineering is presented. This pipeline could be a blue-print for improving kinetically yet limited bioprocesses. Artificial microbial consortia offer functional simplicity, control, and reproducibility. Knowledge-based eco-physiological design is key to eco-biotechnological optimization. Eco-biotechnology optimization depends on mutual medium selection and design. Abstract : In natural microbial ecosystems the metabolic diversity of the organisms enables interaction among the community members and allows them to engage in syntrophic interactions. With regard to biotechnology, artificial microbial consortium engineering is used to improve productivities and yields of bioprocesses. However, to achieve supreme productivity or efficiency at industrial scale, defined ecosystems must be physiologically well-selected to meet eco-biotechnological demands. Here, we present an artificial microbial consortia design and engineering pipeline for developing dark fermentative biohydrogen production processes. The proposed pipeline might be considered as a blue-print for enhancing other bioprocesses that fundamentally face metabolic restrictions or kinetic limitations.